Customer satisfaction in e-commerce: The role of service quality, product quality, and e-servicescape influences via perceived value - Abdella, Rahajeng Ayesha; Indradewa, Rhian (Journal of Management and Digital Business, 2024)
Customer satisfaction was critical for optimizing profitability, especially in e-commerce environments. This study examined the impact of service quality, product quality, and e-servicescape on customer satisfaction in Samsung e-commerce, focusing on perceived value as a mediating variable. This quantitative study employed the Structural Equation Model (SEM). The population in this study consisted of Bekasi city residents who had made at least two purchases from Samsung e-commerce, with 115 respondents selected using a purposive sampling technique. Data was collected via a questionnaire, and KMO and MSA measurements were performed to assess validity. The data supported positive correlations between service quality, product quality, e-servicescape, and customer satisfaction. Furthermore, this study demonstrated that perceived value could mediate the relationship between service quality, product quality, and customer satisfaction.